2014
DOI: 10.1111/luts.12047
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Overactive Bladder Symptoms and Bladder Ischemia with Dutasteride in Patients with Benign Prostatic Enlargement

Abstract: Reduction of obstruction and improvement of bladder ischemia might play an important role in a beneficial impact of dutasteride on overactive bladder symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Silodosin was also reported to improve bladder flow and voiding frequency in a rat atherosclerosis model (Goi et al 2013). In a series of 30 consecutive men with LUTS and unsatisfied with their symptom improvement during α-blocker treatment, a 24-week add-on treatment with dutasteride reduced prostate size, improved LUTS, and reduced the bladder vascular resistive index (Wada et al 2015). Within this study the 20 men reporting persisting urgency, bladder perfusion was improved to a smaller degree than in the 10 without urgency.…”
Section: Effects Of Therapeutics On Bladder Perfusionmentioning
confidence: 97%
“…Silodosin was also reported to improve bladder flow and voiding frequency in a rat atherosclerosis model (Goi et al 2013). In a series of 30 consecutive men with LUTS and unsatisfied with their symptom improvement during α-blocker treatment, a 24-week add-on treatment with dutasteride reduced prostate size, improved LUTS, and reduced the bladder vascular resistive index (Wada et al 2015). Within this study the 20 men reporting persisting urgency, bladder perfusion was improved to a smaller degree than in the 10 without urgency.…”
Section: Effects Of Therapeutics On Bladder Perfusionmentioning
confidence: 97%
“…Regulation of tumor necrosis factor‐like ligand 1a (TL1A) and its receptor DR3 by bladder ischemia and potential roles of TL1A and DR3 in bladder inflammation are documented in the elderly patients 20 . Dutasteride (5α‐reductase inhibitor, antiandrogen) is suggested to reduce OAB symptoms by increasing blood flow and improving bladder ischemia 21 …”
Section: Pelvic Ischemiamentioning
confidence: 99%
“…20 Dutasteride (5α-reductase inhibitor, antiandrogen) is suggested to reduce OAB symptoms by increasing blood flow and improving bladder ischemia. 21 Recently, a study of women consisting of 74 OAB patients and 73 controls showed that all atherosclerosis indicators were significantly associated with OAB and that there was a significant relationship between OAB and decreased bladder neck perfusion. It was also found that OAB correlated with severity of systemic atherosclerosis and with impaired vascular perfusion of the bladder.…”
Section: Bladder Ischemia: the Human Datamentioning
confidence: 99%
“…Therefore, if a patient with BPH receives appropriate treatment for BOO, his OAB symptoms are expected to improve. Prior studies reported that medical treatment, such as with an alpha-blocker or 5-alpha-reductase inhibitor, and surgical treatment via transurethral resection of prostate (TURP) both significantly improve voiding symptoms as well as BPH-induced OAB symptoms [567]. …”
Section: Introductionmentioning
confidence: 99%